Hubungan Antara Aktivitas Fisik Sehari Hari Dengan Tingkat Kebugaran Jasmani Siswa Kelas 7 SMP Shalahuddin - Yuda Purwanto; M.E Winarno (Program Studi Pendidikan Jasmani, Fakultas Pedagogik dan Psikologi (FPeP), 2023)
The purpose of this study was to determine the relationship between physical activity and the level of physical fitness in grade 7 students of SMP Salahuddin Malang grade 7. By using a quantitative descriptive methodology, correlational design, and a sample of 67 students, the independent variable was physical activity (X), and the variable tied is the level of physical fitness (Y By using physical fitness tests such as running tests 50 meter run test, push ups, sit ups, long jump without a prefix, and MFT, as well as physical activity tools such as the PAQ C physical activity questionnaire. The results of physical activity with a high level of physical fitness are better than rtable (0.238). Conclusion: Physical activity and fitness level are positively and significantly related